2001
DOI: 10.1053/joca.2001.0461
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the inflammatory response in the rat TMJ with increasing doses of complete Freund's adjuvant

Abstract: These data suggest that an intermediate dose of CFA can be used to effect submaximal levels of TMJ inflammation that will allow experimental modulation in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 16 publications
5
49
0
1
Order By: Relevance
“…The increased collagen content may be accounted for by the increased cellularity and is likely a hypertrophic response (Abubaker et al, 1996;Okazaki et al, 1996). CFA has been injected into the superior joint compartment in the present and other studies (Harper et al, 2001;Guan et al, 2005;Spears et al, 2005;Flake et al, 2006). In the present study, we observed few phenotypic changes in condylar cartilage.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The increased collagen content may be accounted for by the increased cellularity and is likely a hypertrophic response (Abubaker et al, 1996;Okazaki et al, 1996). CFA has been injected into the superior joint compartment in the present and other studies (Harper et al, 2001;Guan et al, 2005;Spears et al, 2005;Flake et al, 2006). In the present study, we observed few phenotypic changes in condylar cartilage.…”
Section: Discussionsupporting
confidence: 61%
“…CFA is a solution of antigen emulsified in mineral oil and consists of inactivated and dried mycobacteria. CFA injection is simple and reproducibly induces TMJ inflammation, as shown in previous work by us and sustained Inflammation Induces Degeneration of the temporomandibular Joint others with a focus on the acute phase of inflammation (Harper et al, 2001;Guan et al, 2005;Spears et al, 2005;Flake et al, 2006;Lai et al, 2006;Wu et al, 2010;Kou et al, 2011). However, single-dose CFA injections in previous work were primarily associated with transient inflammatory changes in the TMJ.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…However, in 2001 study have mentioned that the fibrocartilage of condyle changed after CFA injection for 2 days 11 . In addition to in 2012 study used CFA to induced arthritis for 35 days, the fibrocartilage of condyle have still maintained its shape and thickness 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The Harderian gland sits behind each orbit in rodents; this gland produces and releases a porphyrin via the nasolacrimal ducts [Harper, Kerins, McIntosh, Spears & Bellinger, 2001]. This chromodacryorrhea dries on the fur creating a reddish stain around the eyes and nose.…”
Section: Analysis Of Chromodacryorrheamentioning
confidence: 99%